KAROSHI (WORK TO DEATH) - Moh. Toriqul Chaer (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2017)
When the tide of unemployment hit the USA and Europe, in Japan the opposite phenomenon occurs. In 2002, in Japan deaths were recorded because of excessive works. In this country, the phenomenon of death because of excessive works is called Karoshi. Karoshi is common in Japan.  It becomes deadly syndrome as a consequence of long hours works. The debate about deaths from excessive work already sticking out in Japan since the 70s. The first official case of Karoshi was reported in 1969 when a 29-year-old male worker died because of stroke. It is estimated over ten thousand workers died each year due to death by brain and stroke caused by an overload work. Karoshi often happen to male workers dominantly. The main cause of karoshi is stress due to high pressure in the work environment, and work habits of exceeding a  standard of normal working time (8 hours). In addition, their extra time to work is imbalance with and the salary they earn. In its development, the phenomenon of karoshi contributes to the term salaryman and workaholic.